STUDI BIOAKUMULASI ION LOGAM Pb DALAM RAMBUT DAN DARAH OPERATOR STASIUN PENGISIAN BAHAN BAKAR UMUM, JALAN SENTOSA, SAMARINDA - Sukma Wiratama; Saibun Sitorus; Rudi Kartika (JURNAL ATOMIK, 2018)
A study about Bioaccumulation of Pb Metal Ion in Hair and Blood of Operator of General Fuel Filling Station, Sentosa Road Samarinda has been conducted. The aim of the study is to determine the accumulation of Pb metal ions levels and the association between the hours of work of gas station operator assumed to be positively correlated and the levels of Pb metal ions in hair as well as in blood. Hair and blood were homogenized and analyzed by Atomic Adsorption Spectrophotometer (AAS). The results displayed that the lowest and highest level of Pb metal ions contained in hair was 0.03 μg/g and 0.07 μg/g, respectively. The highest number found in blood was similar to the level contained in hair, that is 0.07 μg/mL. However, the lowest level was marginally lower with a number 0.01 μg/mL. The coefficient correlation (r) obtained were 0.822 and 0.859 for hair and blood, respectively. These numbers indicate there was a strong positive relationship between working hours of gas station operator and levels of Pb metal ion in hair and blood. This inference was also supported by the results of t test, that is, 0.564. Furthermore,% determinants analysis was also undertaken which result in 82.2% and 85.9% for hair and blood, respectively to strengthen the test result that working hours of gas station operator in Sentosa Road Samarinda was positively associated with Pb metal ion levels in hair and in blood.